Icodextrin versus Glucose 2.5% on markers of hypervolemia and survival of patients undergoing automated peritoneal dialysis with an unplanned start: a randomized controlled trial - Azevedo, Leonardo Sotello [UNESP]; Banin, Vanessa Burgugi [UNESP]; Dias, Dayana Bitencourt [UNESP]; Mendes, Marcela Lara [UNESP]; Alves, Camila Albuquerque [UNESP]; Silva, Maryanne Zilli Canedo [UNESP]; Moraes, Thyago Proença de; Ponce, Daniela [UNESP] (Sociedade Beneficente Israelita Brasileira Hospital Albert Einstein, 2024)
OBJECTIVE: The efficacy of icodextrin versus glucose patients undergoing peritoneal dialysis remains unclear. The study was designed to compare the effects of once-daily long-dwell icodextrin versus glucose on markers of hypervolemia and survival among patients with kidney failure undergoing an unplanned initiation of automated peritoneal dialysis. METHODS: This was a randomized, non-blinded, and prospective controlled study. Prevalent and stable patients undergoing automated peritoneal dialysis with a recent peritoneal equilibration test showing a dialysate/plasma creatinine of >0.50 were randomized to receive either 7.5% icodextrin or 2.5% glucose solution. Patients were evaluated at baseline (one month after the start of peritoneal dialysis), 3 months, and 6 months after inclusion. The peritoneal dialysis solution was used for at least 3 months, with a follow-up period of 24 months. RESULTS: Thirty patients were enrolled. There were no baseline differences between the groups. During the study period, patients in the Icodextrin Group showed improvements in the phase angle and ultrafiltration, whereas there were no changes in the Glucose Group. Additionally, extracellular water was significantly lower in the Icodextrin Group at the end of the study than at baseline. No statistical differences between the two groups were observed in urine volume, ultrafiltration, extracellular water, phase angle, renal creatinine clearance, use of diuretics and antihypertensives, or blood pressure. During the 24-month follow-up, the number of events related to overall mortality was seven (Icodextrin Group, n=4; Glucose Group, n=3), with no difference between the groups for this outcome or technique survival. CONCLUSION: Icodextrin significantly improved ultrafiltration, extracellular water, and phase angle at the end of the study compared to baseline in patients on the urgent start of automated peritoneal dialysis. REGISTRY OF CLINICAL TRIALS: (www.ctri.nic.in) under the number RBR-97z4wh6.